background image

Obvious.

⇐ A

is connected regarding

RLD

(Ob

f

;Ob

f

)

F

iff

S

(

F

) =

F

0

F

1

F

2

. . .

up

A ×

RLD

A

.

S

(

f

) =

RLD

(Ob

µ

;Ob

µ

)

S

(

F

)

|

F

up

f

 

A ×

RLD

A |

F

up

f

 

=

A ×

RLD

A

.

Conjecture 22

A filter object

A

is connected regarding a funcoid

µ

iff

A

is

connected for every

F

FCD

(Ob

µ

;Ob

µ

)

up

µ

.

The above conjecture is open even for the case when

A

is a principal f.o.

Conjecture 23

A filter object

A

is connected regarding a reloid

f

iff it is con-

nected regarding the funcoid

(

FCD

)

f

.

The above conjecture is true in the special case of principal filters:

Proposition 50

A f.o.

Ob

µ

A

(for a set

A

) is connected regarding an endo-

reloid

f

iff it is connected regarding the endo-funcoid

(

FCD

)

f

.

Proof

Ob

f

A

is connected regarding a reloid

f

iff

A

is connected regard-

ing every

F

up

f

that is when (taken in account that connectedness for

RLD

(Ob

f

;Ob

f

)

F

is the same as connectedness of

FCD

(Ob

f

;Ob

f

)

F

)

F

up

f

∀X

,

Y ∈

F

(Ob

f

)

\

n

0

F

(Ob

f

)

o

: (

X ∪ Y

=

Ob

f

A

⇒ X

h

FCD

(Ob

f

;Ob

f

)

F

i

Y

)

∀X

,

Y ∈

F

(Ob

f

)

\

n

0

F

(Ob

f

)

o

F

up

f

: (

X ∪ Y

=

Ob

f

A

⇒ X

h

FCD

(Ob

f

;Ob

f

)

F

i

Y

)

∀X

,

Y ∈

F

(Ob

f

)

\

n

0

F

(Ob

f

)

o

: (

X ∪ Y

=

Ob

f

A

⇒ ∀

F

up

f

:

X

h

FCD

(Ob

f

;Ob

f

)

F

i

Y

)

∀X

,

Y ∈

F

(Ob

f

)

\

n

0

F

(Ob

f

)

o

: (

X ∪ Y

=

Ob

f

A

⇒ X

[(

FCD

)

f

]

Y

)

that is when the set

Ob

f

A

is connected regarding the funcoid (

FCD

)

f

.

7.5

Algebraic properties of

S

and

S

Theorem 77

S

(

S

(

f

)) =

S

(

f

)

for every endo-reloid

f

.

Proof

S

(

S

(

f

)) =

RLD

(Ob

f

;Ob

f

)

S

(

R

)

|

R

up

S

(

f

)

 

RLD

(Ob

f

;Ob

f

)

S

(

R

)

|

R

∈ {

S

(

F

)

|

F

up

f

}

 

=

RLD

(Ob

f

;Ob

f

)

S

(

S

(

F

))

|

F

up

f

 

=

RLD

(Ob

f

;Ob

f

)

S

(

F

)

|

F

up

f

 

=

S

(

f

).

So

S

(

S

(

f

))

S

(

f

). That

S

(

S

(

f

))

S

(

f

) is obvious.

Corollary 21

S

(

S

(

f

)) =

S

(

S

(

f

)) =

S

(

f

)

for any endo-reloid

f

.

69